Examining How Talent Management Practices Influence the Inclination of Research Scientists in the Realm of Disruptive Innovation Within the Pharmaceutical R&D Sector - Mohinder, Shakambri (Digital Repository of Theses - SSBM Geneva, 2024)
This dissertation delves into the pivotal role of Talent Management practices in molding the innovation behaviors of research scientists within the pharmaceutical R&D sector, emphasizing the criticality of disruptive innovation. Set against the backdrop of India's burgeoning prominence in the global science and innovation arena, this study meticulously explores the multifaceted challenges organizations encounter in their quest to manage and sustain a workforce capable of pioneering groundbreaking innovations. By harnessing an exploratory research methodology that integrates both quantitative and qualitative data analyses, the study unveils a comprehensive Talent Sustainability Framework (TSF). This innovative framework delineates several key factors—leadership, organizational culture, strategic alignment, continuous learning, and effective networking, alongside robust talent management practices—as quintessential for the sustenance of a highly innovative talent pool. Rooted in a blend of inductive and deductive reasoning, the research provides an insightful exploration of the synergistic interplay between various internal organizational elements and their profound impact on fostering a conducive environment for talent sustainability. The empirical findings underscore the significant influence of these internal factors in promoting a sustainable talent ecosystem within the pharmaceutical R&D sector, marking a notable contribution to the existing literature on talent management within scientific research domains. Furthermore, the study's outcomes highlight the indispensable nature of cultivating and retaining top-tier talent as a linchpin for organizational success and competitiveness in the ever-evolving landscape of global innovation. By offering a novel perspective on the dynamics of talent management in facilitating disruptive innovation, this dissertation not only underscores the imperative of nurturing and preserving skilled personnel but also lays a solid groundwork for subsequent inquiries into talent sustainability within knowledge-intensive industries.